2018
DOI: 10.1038/s41598-018-34383-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential recognition of Haemophilus influenzae whole bacterial cells and isolated lipooligosaccharides by galactose-specific lectins

Abstract: Bacterial surfaces are decorated with carbohydrate structures that may serve as ligands for host receptors. Based on their ability to recognize specific sugar epitopes, plant lectins are extensively used for bacteria typing. We previously observed that the galactose-specific agglutinins from Ricinus communis (RCA) and Viscum album (VAA) exhibited differential binding to nontypeable Haemophilus influenzae (NTHi) clinical isolates, their binding being distinctly affected by truncation of the lipooligosaccharide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…Each Hep of the inner core can be a point for addition of strain-specific and phase-variable short carbohydrate extensions that constitute the outer core, which may also mimic host glycan epitopes and could potentially serve as galectin ligand. Other carbohydrate structures on the bacterial surface might also be recognized, as was inferred in a previous study on the binding of two model galactose-specific lectins to NTHi entire cells and isolated LOSs [ 18 ].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Each Hep of the inner core can be a point for addition of strain-specific and phase-variable short carbohydrate extensions that constitute the outer core, which may also mimic host glycan epitopes and could potentially serve as galectin ligand. Other carbohydrate structures on the bacterial surface might also be recognized, as was inferred in a previous study on the binding of two model galactose-specific lectins to NTHi entire cells and isolated LOSs [ 18 ].…”
Section: Introductionmentioning
confidence: 82%
“…Recognition of the high molecular weight adhesin HMW1 by the galactose-specific agglutinin VAA was inferred in a previous study in which the binding of this lectin to NTHi strains expressing HMW1 or not was comparatively examined [ 18 ]. HMW1 is glycosylated at multiple sites with N-linked Gal/Gal-Glc units [ 39 ], and it is expressed by the particular NTHi strain studied here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the absence of the Galα(1-4)Galβ epitope from the chain extension linked to the distal manno-heptose of the Hep trisaccharide inner core ( Figure 5) resulted in decreased binding of VAA but had no significant effect on the binding of RCA, suggesting that RCA might not bind this LOS. Indeed, a follow up study using microarrays containing the purified LOS showed only marginal binding of RCA as opposed to strong binding of VAA, which was drastically reduced for a truncated LOS lacking Galα(1-4)Galβ (Kalograiaki et al, 2018c). In striking contrast, RCA bound strongly to the microarray-printed LOS from the capsule-deficient H. influenzae laboratory strain RdKW20, whose major glycoform displays terminal Galβ(1-4)Glc at the distal Hep extension, while, although ∼19% of this LOS bears terminal Galα(1-4)Galβ, VAA bound only weakly.…”
Section: Bacteria Microarrays For Examining Bacterial Surface Glycansmentioning
confidence: 99%
“…In-depth analysis of the LOS epitopes recognized by RCA and VAA in each case, using STD-NMR experiments assisted by molecular dynamics simulations, revealed that RCA bound the RdKW20 LOS glycoform displaying terminal Galβ(1-4)Glcβ, whereas VAA recognized the Galα(1-4)Galβ(1-4)Glcβ epitope ( Figure 5) in NTHi375 LOS but not in RdKW20 LOS, what could be due to different conformational preferences of the branch and ensuing presentation of the epitope. Binding assays to wild type and selected mutant/transformed whole bacterial cells ran in parallel revealed that, besides the LOS, other carbohydrate structures on the bacterial surface serve as lectin ligands, and highlighted the impact of the specific display of cell surface components on lectin binding, stressing the importance of examining binding to entire bacterial cells (Kalograiaki et al, 2018c).…”
Section: Bacteria Microarrays For Examining Bacterial Surface Glycansmentioning
confidence: 99%